AN ANALYSIS OF SPEECH ACTS USED BY LECTURERS OF ENGLISH EDUCATION DEPARTMENT OF UNDIKSHA IN THE ACADEMIC YEAR OF 2013/2014 - ., Gede Surya Ulandara; ., Prof. Dr.I Ketut Seken,MA; ., Putu Eka Dambayana S., S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
ABSTRACT This study was conducted to identify kinds of speech acts produced by the lecturers of English Education Department of Undiksha during the teaching and learning process and identify the instructional functions of those kinds of speech acts. The subjects of this study were 2 lecturers who taught the first semester students of English Education Department of UNDIKSHA Singaraja in academic year 2013/2014. This study was a qualitative study and was conducted in the classroom during the teaching and learning process by two lecturers of English Education Department UNDIKSHA. The data were obtained through recording, interview and also observation. The data collected were the lecturers’ utterances. They were transcribed, selected and reduced until the data needed were found. Then, the data obtained were descriptively analyzed. The findings of the study showed that the lecturers used representative, directive, commisive, expressive and declarative speech acts in the classroom. Based on 121 example utterances, lecturers mostly used directive speech acts, it was 41.32%of 121 utterances. According to the interview, it was also found that lecturers uttered directive speech acts in order to make students clearly understood the meaning and avoid understanding. Thus, it was very important for students to understand what lecturers/teacher uttered to avoid misconceptions, miscommunication or misunderstanding.Kata Kunci : Key Terms: utterances, speech acts ABSTRAK Penelitian ini dilaksanakan untuk mengidentifikasi jenis tindak tutur yang diucapkan oleh dosen Jurusan Pendidikan Bahasa Inggris UNDIKSHA saat kegiatan belajar mengajar dan juga mengidentifikasi fungsi pengajaran dari jenis tindak tutur tersebut. Subyek penelitian ini adalah 2 dosen yang mengajar mahasiswa semester satu Jurusan Bahasa Inggris UNDIKSHA Singaraja tahun ajaran 2013/2014. Penilitian ini merupakan penelitian kualitatif. Penelitian ini dilakukan di dalam kelas saat pengajaran dilakukan oleh kedua dosen di Jurusan Pendidikan Bahasa Inggiris UNDIKSHA. Data didapatkan melalui perekaman, wawancara dan observasi.Data yang dikkumpulkan merupakan ucapan dosen. Semua itu dideskripsikan, dipilih dan dikurangi hingga data yang diperlukan diperoleh. Kemudian, data yang diperoleh dianalisis secara deskriptif. Temuan penelitian ini menunjukkan bahwa dosen menggunakan tindak tutur berupa representative, directive, commisive, expressive dan declarative. Berdasarkan 121 contoh ucapan dosen, dosen lebih sering menggunakan tindak tutur directive, yaitu 41.32% dari 121 sample. Sesuai dengan hasil wawancara, juga ditemukan bahwa dosen menggunakan tindak tutur directive dengan tujuan membuat siswa lebih mudah memahami dan menghindari kesalahpahaman. Sehingga, sangatlah penting agar mahasiswa memahami apa yang dosen ucapkan untuk menghindari konsep, komunikasi dan pemahaman yang salah.keyword : Key Terms: ucapan, tindak tutur